Pengawasan Dan Penindakan Terhadap Warga Negara Asing Yang Kehabisan Dana Perjalanan Wisata Berdasarkan Pasal 66 Ayat (2) Huruf B Undang-Undang Nomor 6 Tahun 2011 Tentang Keimigrasian (Studi di Kantor Imigrasi Kelas I Khusus TPI Ngurah Rai): Supervision and Measures regarding Foreign Tourists running out of Money during their Travel Period according to Article 66 Paragraph (2) Letter B of Law Number 6 of 2011 concerning Immigration (A study in Immigration Office Class I of immigration check of N - Ray, Puteri Maharani (Brawijaya Law Student Journal, 2020)
Yafie Abigail Pratama, Reka Dewantara, Ranitya Ganindha Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No. 169 Malang Email : yafiepratama@gmail.com Abstract The authority of the Bank of Indonesia as the Central Bank of the Republic of Indonesia is contained in Article 4 (1) of the Act on Amendments to the Law No. 23 of 1999 on Bank Indonesia. Based on Article 4 (2) of Act No. 3 of 2004, which states that the Bank is an Independent State Institution. Rupees' value stability is reflected in inflation and exchange rates. The Bank of Indonesia has established the BI-7 Dyas Reverse Repo Rate policy as a regulatory framework for monetary operations in order to the Bank's goals. This study analyses whether the implementation of the Bank Indonesia -7 Days Reverse Repo Rate policy as a framework for regulating monetary operations in realizing the stability of the currency exchange rate. Based on the results of the research through the Purposive Sampling method, the policy of Bank Indonesia-7 Days Reverse Repo rate has effectively achieved the planned objectives, the jurisdictional obstacle in its implementation is in the lack of harmonization between the Department of Economic and Monetary Policy and the Law Department, while the non-legal obstacles are influenced by external factors of Bank Indonesian namely the global economic and geopolitical conditions. The Bank of Indonesia overcomes the obstacles with its monetary operations strategy, one of which is through the Board of Governors Meeting and the Tri-Year and Annual Report. Together, the Bank of Indonesia coordinates with the Central Government on the integration of monetary policy with policy. Keywords: Bank Indonesia -7 Days Reverse Repo Rate, Bank Indonesia, Monetary Policy Abstrak Penelitian ini bertujuan untuk mengetahui pengawasan dan tindakan terhadap wisatawan asing yang kehabisan uang selama masa perjalanannya sesuai Pasal 66 ayat (2) huruf b Undang-Undang Nomor 6 Tahun 2011 tentang Keimigrasian oleh Kantor Imigrasi Kelas I untuk pemeriksaan keimigrasian di Ngurah Rai pada tahun 2011. Bali dan kendala yang dihadapi serta tindakan yang diambil dalam pengawasan dan sanksi terkait permasalahan ini. Hasil penelitian mengungkapkan bahwa Kantor Imigrasi Kelas I pada pemeriksaan imigrasi Ngurah Rai telah melakukan pengawasan fungsional sesuai kewenangannya sebagaimana dijamin dalam Pasal 66 ayat (2) huruf b Undang-Undang Nomor 6 Tahun 2011 tentang Keimigrasian. Staf fungsional melakukan pengawasan eksternal karena pengawasan di Kantor Imigrasi Kelas I Ngurah Rai Bali dilakukan oleh aparat di luar pemerintah atau non eksekutif terhadap wisatawan asing yang kehabisan uang. Permasalahannya, tidak semua wisatawan asing memahami betul masa tinggal yang diperbolehkan di Indonesia, begitu pula bagi pengelola akomodasi yang sebagian besar dari mereka belum memahami cara menggunakan aplikasi yang ditujukan untuk melaporkan masa tinggal orang asing tersebut. Telah ada pengenalan aplikasi yang harus digunakan oleh wisatawan asing dengan izin tinggal terbatas untuk membantu mereka tetap waspada terhadap jumlah masa menginap, dan pengenalan ini juga harus berlaku untuk manajer akomodasi. Kata Kunci: Warga Negara Asing, Perjalanan Wisata, Keimigrasian